2016
DOI: 10.1111/pace.12958
|View full text |Cite
|
Sign up to set email alerts
|

Severe Spontaneous Echo Contrast/Auricolar Thrombosis in “Nonvalvular” AF: Value of Thromboembolic Risk Scores

Abstract: In patients with persistent AF and suboptimal anticoagulation, a risk score composed by history of heart failure, high CRP, and female gender identifies patients at high risk of left atrial SEC/thrombosis when its value is >1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…However, it is still controversial whether the CHADS2/ CHA2DS2-VASc score is an independent risk factor for LAT/SEC. Several studies showed the score was not an independent risk factor for LAT/SEC [11,19,22], and had a modest value for predicting LAT/SEC in most studies [12,20,22,23]. These discrepancies might be due to the following reasons: (1) the development of LAT/SEC is closely associated with the matrix and function of the left atrium [24,25], which has different associations with the components of the CHADS2/CHA2DS2-VASc score.…”
Section: Discussionmentioning
confidence: 90%
“…However, it is still controversial whether the CHADS2/ CHA2DS2-VASc score is an independent risk factor for LAT/SEC. Several studies showed the score was not an independent risk factor for LAT/SEC [11,19,22], and had a modest value for predicting LAT/SEC in most studies [12,20,22,23]. These discrepancies might be due to the following reasons: (1) the development of LAT/SEC is closely associated with the matrix and function of the left atrium [24,25], which has different associations with the components of the CHADS2/CHA2DS2-VASc score.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have identified several predictive biomarkers for SEC occurrence, such as fibrinogen, C-reactive protein, D-dimer, and some inflammatory biomarkers. 21 36 However, these predictors were obtained by comparing patients with SEC and control, and therefore were not necessarily predictive of SEC severity. The core mechanism for SEC was the aggregation of erythrocytes caused by the compromise of electrostatic repulsion or the formation of intercellular bridging.…”
Section: Discussionmentioning
confidence: 99%
“…Several surrogate markers based on left atrial dilatation or cardiac function have been proposed for risk stratification of cardiogenic stroke. [15][16][17][18][19][20] However, there has been no study in which those surrogate markers were analyzed in Japanese patients in whom catheter ablation was planned. The aim of this study was to determine simple and practical variables in addition to CHADS2 score that enable prediction of patients at high risk for stroke.…”
Section: Introductionmentioning
confidence: 99%